Dynamics of c-kit immunopositive pancreatic beta cells influenced by exogenous factors or endogenous pathology - T. V. Ivanenko; Yu. M. Kolesnyk; A. V. Abramov (Zaporožskij Medicinskij Žurnal)
Mechanisms of beta-endocrinocyte differentiation involving c-kit may be associated with a number of processes, including signaling pathways and regulatory mechanisms. Such factors as activation of the c-kit signaling pathway, an increase or decrease in cell proliferation and survival, regulation of differentiation gene programs and stem cells are important in controlling self-preservation and regulating the cellular number and types, that are differentiated being impacted by intermittent hypoxic hypoxia, hypertension and diabetes mellitus.